Karakteristik Kimia dan Sensori Roti Kering Bagelen Substitusi Tepung Kacang Arab (Cicer arietinum) - Zazti Kinasih; Noli Novidahlia; Muhammad Fakih Kurniawan (Universitas Djuanda, 2023)
Wheat flour is highly used as a main material of processing bread, one of the developments is bagelen bread. The intent of this study is to innovate bagelen dried-bread product with the proportion of chickpea flour, increasing protein (based on SNI) and fibre content. This research was using a one-factor Complete Randomized Design (RAL) method, 2 repeats, with wheat flour: chickpea flour treatment rates each are 100%:0%, 90%:10%, 80%:20%, 70%:30%. ANOVA variance and Duncan test were carried out with a 95% confidence interval. The results of the data analysis stated that the substitution of chickpea flour had a significant effect on protein and fibre level, sensory and hedonic quality, but it has no noticeable effect on the moisture level. The selected product is bagelen dried-bread with the proportion of 80% wheat flour and 20% chickpea flour with moisture content of 6,09%, protein 9,93%, crude fibre 29,5%, ash 1.49%, fat 29.97%, carbohydrate 52.50%, total calorie value of 519,53 kcal. Based on the results of sensory quality tests, bagelen dried-bread was obtained with more brownish-yellowish color, bagelen smell, chickpea smell, baked smell, not smelled langu, tasted sweet like bagelen, chickpea taste, more crispy texture. By hedonic tests, panelists tend to like the color, odor, taste, crispiness, and overalls of the product.